Mengidentifikasi dan Menanggulangi Risiko di PT.XYZ Menggunakan Metode Hirarc - Akbar Maulana Firmansyah; Minto Waluyo (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
XYZ as a company that produces ships and maintains ships is a very important company in the maritime world. This company has several divisions, especially the QHSE (Quality, Health, Safety, Environment) division. The QHSE department has an obligation to maintain safety in work areas, such as new building areas. Therefore, the HIRARC Method is used to identify hazards, assess risks, and mitigate risks. In this research, the HIRARC method is used to analyze the level of risk at the new PT. The results of the study show that the criteria for moderate risk are 2, high is 7, and extreme is 7. This shows the need for treatment at new building stations in order to reduce the level of work accidents.